Morphology and properties of thin-walled microcellular polycarbonate/acrylonitrile–butadiene–styrene blend foam. (July 2019) - Lu, Yuemei; Yang, Mengjin; Liu, Jianren
Microcellular plastics not only have excellent performance, but also can form thin-walled parts. In the paper, the thin-walled microcellular parts (notebook computershell) made of polycarbonate/acrylonitrile–butadiene–styrene blends (PC/ABS) were prepared by foam injection molding with supercritical nitrogen. The morphologies were observed by optical microscope, scanning electron microscope, and optical profiler. The properties (macro-density, impact toughness, thermal conductivity) of the samples were further studied. The results showed that the average cell diameter of the PC/ABS foam was 0.401 µm. The cell density reached 3.25 × 10 12 cell/cm 3 . Compared with unfoamed part, the macro-density of the microcellular part was reduced by 10.9%. Impact toughness of the polycarbonate/acrylonitrile-butadiene-styrene blend (PC/ABS) foam reached 19.9 kJ/m, approximately 2.7 times as great as that of unfoamed part. This may be ascribed that microcellular structure could absorb impact energy resulting in the improvement of toughness. The microcellular structure could also reduce thermal conductivity of the PC/ABS foam. In short, the thin-walled microcellular PC/ABS part with light weight and good toughness could be formed by injection molding with supercritical nitrogen.